THE VIEWPOINT OF INTERNATIONAL STUDENTS USING DINGTALK APP FOR ONLINE LEARNING: AN ETHNOGRAPHY CASE STUDY AND PHOTOVOICE - NICO IRAWAN (State University of Medan, 2023)
This study investigates how students perceive their English-speaking ability after taking online classes using the DingTalk app. Using an ethnographic case study and photovoice, data from international students who enrolled at a Thai public university were evaluated to shed light on how students rate their use of English in online classrooms. During the pandemic, student activities with online learning emerged as a lived experience, indicating a convergence of student concerns. The primary aspects of these issues include student expectations for the time and space of online learning, self-motivation, and the participation of others, especially international students and the faculty member's ability to communicate effectively. Ultimately, international student engagement is determined by the congruence between the student's expectations regarding these dimensions and the student's overarching educational and personal goals for enrolling in the course.